Aktivitas Bermain sebagai Strategi Koping untuk Meningkatkan Kebahagiaan pada Siswa Sanggar Bimbingan Kampung Baru Malaysia - Yudi Kurniawan; Faisal Yusuf; Sinta Pramucitra; Citra Andriani Kusumawati; Guruh Mulia Widayat; Anandha Anandha (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to apply play activities as a coping strategy to increase happiness in students at Sanggar Bimbingan Kampung Baru Kuala Lumpur Malaysia. Play activities play an important role in supporting children's social, emotional, and cognitive development. This program was carried out for one session with a duration of 90 minutes, involving 57 students aged 7–12 years. The methods used included creative games such as storytelling and singing, which were designed to create a fun atmosphere, train social skills, and provide space for free expression of emotions. The results of observations showed an increase in student happiness as indicated by active participation, cheerful expressions, and positive interactions between students during the activity. The results of interviews revealed positive impacts such as reduced emotional stress, increased self-confidence, and better learning motivation. Play activities have proven to be effective as a simple coping strategy that can be implemented in non-formal learning environments to support children's mental health and well-being. This program is expected to be a model for sustainable psychosocial interventions in similar communities.